الترميم بالنسج الرخوة والصلبة بعد الزرع الفوري للقواطع العلوية بتقنيات مختلفة, دراسة سريرية - عبد الحق, جواد; أبو عسلي, إياد (Latakia University Journal -Medical Sciences Series, 2019)
Aesthetic restoration of anterior teeth in maxila after immediate implant placement is one of the most difficult procedures to execute. Resorption of the buccal wall of the extraction socket may lead to significant disadvantages, especially in the anterior part of the maxilla. İn this case report we insert implants immediatly in fresh Socket. fenestrations or dehiscences of the bone walls and a residual gap between implant surfaces and surrounding bone walls were augmented with bone greft. An average facial gingival tissue recession of 1 mm is still common after one year of function in immediate implantion. The purpose of this clinical article is to describe a grafting technique using subepithelial connective tissue grafts and free gingival palatal graft to recontour soft-tissue margin discrepancy for implants restorations after 10 month of immediat placement in the anterior maxilla. إن تأمين الناحية التجميلية للأسنان الأمامية في الفك العلوي بعد الزرع الفوري هو واحد من أكثر الإجراءات صعوبة. إن امتصاص الجدار الدهليزي للسنخ العظمي بعد القلع يؤدي إلى عيوب كبيرة ، لا سيما في الجزء الأمامي من الفك العلوي. في هذه الحالة السريرية نقوم بزرع فوري في الأسناخ العظمية بعد القلع . تمت معالجة العيوب العظمية لجدران السنخ أو الفراغ المتبقي ماحول الزرعة باستخدام الطعوم العظمية. إن الانحسار اللثوي بمعدل 1 ملم ما زال شائعا بعد عام واحد من الاستخدام الوظيفي للزرعة. تهدف هذه الحالة السريرية لوصف اسلوب التطعيم باستخدام الطعم الضام والبشري لاعادة تشكيل الأنسجة الرخوة حول زرعات الأسنان الأمامية الفورية بعد 10 أشهر.